Endangered spined loach Cobitis species in Southwest Germany: A complex network of native, hybrid and newly emerged populations - Samuel Roch; Patrick Bartolin; Pascal Vonlanthen; Jan Baer; Simon Grundmüller; Laura S. Epp; Alexander Brinker (Fisheries Management and Ecology, 2023)
Successful conservation of cryptic species such as representatives of the genus Cobitis presents a challenge for fishery managers. Only Cobitis taenia L. is currently assumed to occur in southwest Germany, where it is classified as critically endangered. Established genetic markers and eDNA analysis identified three Cobitis species in the study area. Cobitis taenia and Cobitis elongatoides were widely distributed in the Rhine River system, primarily forming hybrid species complexes in which polyploid individuals dominate but coexist with diploid parent species. A third non‐native species, Cobitis bilineata , has recently become established in the southern part of the Rhine to which it probably migrated naturally via the connected Aare River system. In the Danube River catchment, two populations, including one previously thought to be extinct, comprise both diploid and polyploid representatives of C. elongatoides . Our results provide an important basis for more targeted conservation strategies for Cobitis species currently found in the region.

A taxonomic revision of the whitefish of Lakes Brienz and Thun, Switzerland, with description of three new species. - Oliver Selz; Ole Seehausen; Carmela Dönz; Pascal Vonlanthen (Frontiers in Marine Science, 2019)

Population structure, inbreeding and local adaptation within an endangered riverine specialist: the nase (Chondrostoma nasus) - Alan G. Hudson; Pascal Vonlanthen; Ole Seehausen (Conservation Genetics, 2014)

Speciation leads to divergent methylmercury accumulation in sympatric whitefish - Nanina Blank; Alan G. Hudson; Pascal Vonlanthen; Ole Seehausen; Chad R. Hammerschmidt; David B. Senn (Aquatic Sciences, 2013)

Colonization history of the Swiss Rhine basin by the bullhead ( Cottus gobio ): inference under a Bayesian spatially explicit framework - SAMUEL NEUENSCHWANDER; CARLO R. LARGIADÈR; NICOLAS RAY; MATHIAS CURRAT; PASCAL VONLANTHEN; LAURENT EXCOFFIER (Molecular Ecology, 2008)
The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20 000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead ( Cottus gobio ), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molecular diversity of eight sampled populations is simulated and compared to observed data at six microsatellite loci under an approximate Bayesian computation framework to estimate the parameters of the colonization process. Our demographic estimates fit well with current knowledge about the biology of this species, but they suggest that the Swiss Rhine basin was colonized very recently, after the Younger Dryas some 6600 years ago. We discuss the implication of this result, as well as the strengths and limits of the spatially explicit approach coupled to the approximate Bayesian computation framework.

Assessment of fish health status in four Swiss rivers showing a decline of brown trout catches - Simone Zimmerli; Daniel Bernet; Patricia Burkhardt-Holm; Heike Schmidt-Posthaus; Pascal Vonlanthen; Thomas Wahli; Helmut Segner (Aquatic Sciences, 2007)